KERAMIK GANESHA F. WIDAYANTO DALAM PERSPEKTIF STRUKTURALISME LEVI-STRAUSS’ - Indro Baskoro Miko Putro, S.Sn. (Ars: Jurnal Seni Rupa dan Desain, 2006)
Ceramics o f Ganesha by F. Widayaitto represent the expressive works o f art, which different fromthe sculptures o f Ganesha as the deity in Hindu mythology during Hie time we recognized. Pursuant tocharacteristic exist in both, and so its can be detailed and then be compared to and analyzed. One o f thecorrect perspectives to analyze these kinds o f expressive arts is the Structuralism perspective i f Levi-Strauss. I low this paradigm can decompose and give the solutions to the problems o f expression arl will beformulated later in this article.Key words: Ceramics, Ganesha, The expressive works o f art, Hindu mythology, The Structuralismperspective o f Levi-Strauss.